Predictors of muscularity‐oriented disordered eating behaviors in U.S. young adults: A prospective cohort study. Issue 12 (20th June 2019) - Nagata, Jason M.; Murray, Stuart B.; Bibbins‐Domingo, Kirsten; Garber, Andrea K.; Mitchison, Deborah; Griffiths, Scott
Abstract: Objective: To determine adolescent predictors of muscularity‐oriented disordered eating behaviors in young men and women using a nationally representative longitudinal sample in the United States and to examine differences by sex. Method: We used nationally representative longitudinal cohort data collected from baseline (11–18 years old, 1994–1995) and 7‐year follow‐up (18–24 years old, 2001–2002) of the National Longitudinal Study of Adolescent to Adult Health. We examined adolescent demographic, behavioral, and mental health predictors of young adult muscularity‐oriented disordered eating behaviors defined as eating more or differently to gain weight or bulk up, supplements to gain weight or bulk up, or androgenic anabolic steroid use at 7‐year follow‐up. Results: Of the 14, 891 included participants, 22% of males and 5% of females reported any muscularity‐oriented disordered eating behavior at follow‐up in young adulthood. Factors recorded at adolescence that were prospectively associated with higher odds of muscularity‐oriented disordered eating in both sexes included black race, exercising to gain weight, self‐perception of being underweight, and lower body mass index z ‐score. In addition, participation in weightlifting; roller‐blading, roller‐skating, skate‐boarding, or bicycling; and alcohol among males and depressive symptoms among females during adolescence were associated with higher odds of muscularity‐oriented disordered eating in young adulthood. Conclusions: Interventions to prevent muscularity‐oriented disordered eating behaviors may target at‐risk youth, particularly those of black race or who engage in exercise to gain weight. Future research should examine longitudinal health outcomes associated with muscularity‐oriented disordered eating behaviors.